Uji Toksisitas Sub Akut Infusa Daun Afrika(Vernonina amygdalina Del.) terhadap Histopatologi HatiMencit (Mus musculus) Galur Balb/C - Wafa Aufia; Surya Amal; Nurul Marfu'ah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2018)
Allah created everything in this world has its benefits, including plants. African Bitter Leaves (Vernonia amygdalina Del.) is an herbal plant that has been experimented as anticancer, antioxidant, antidiabetic and analgesic with the presence of sesquiterpene lactones, saponins, alkaloids, tannins, polyphenol, monoterpene, Quinones, and Saponins. It is employed as an herbal medicine in infuse preparations. This study aims to investigate the safety standard and the effects of African Bitter Leaves infuse (Vernonia amygdalina Del.) againts the liver histopathology in mice strain BALB/c. This study is an experimental research using Completely Randomized Design (CRD). The practices are grouped into 4 different with 3 times repeatedly. The practices given, among others, control (Aquades 0.25 ml), P1 (doses of 10% b/v), P2 (doses of 20% b/v) and P3 (doses of 30% b/v). The observed object is the liver histopathology in mice strain BALB/c at the centrilobular area, midlobular and periportal, then analysis by one-way ANOVA followed by Tukey's Post hoc test. The results of this study stated that the doses of 10% b/v destroyed 24% cell degeneration and 9% cell necrosis, at a dose of 20% b/v destroyed 53% cell degeneration and 21% cell necrosis, and at doses of 30% b/v destroyed 55% cell degeneration and 40% cell necrosis. Based on ANOVA results it can be concluded that the African Bitter Leaves infuse influence liver histopathology in mice strains BALB/c. Destroyed of liver histology include degenerate cells at doses 10% b/v, 20% b/v, 30% b/v, and necrosis cell at doses 20% b/v and 30% b/v.